ANALYSIS OF STUDENTS' CRITICAL THINKING SKILL THROUGH ONLINE LEARNING ASSISTED BY STUDENT WORKSHEETS - Lilis Lismaya; Agus Priyanto; Anni Samarotul Khairiyah (Universitas Kuningan, 2021)
This research is motivated by the lack of teaching materials that can facilitate students' critical thinking skills in learning during the COVID-19 pandemic. Critical thinking skills are very important competencies to be trained. This ability is indispensable in everyday life. The purpose of this study was to analyze critical thinking skills through online learning assisted by student worksheets. The method used in this research is Quasi Experiment with pre-test-post-test control group design. The population in this study were students of class XI MIPA at SMA Negeri 1 Cigugur for the academic year 2020/2021. The sample used in this study consisted of 50 students, consisting of 2 classes, namely the experimental class and the control class. The sampling technique used is purposive sampling. The instruments used are critical thinking questions and student response questionnaires to the implementation of online learning assisted by student worksheets. Based on the results of analysis and calculations with hypothesis testing, the results obtained are H1 is accepted and Ho is rejected, meaning that students' critical thinking skills increase in online learning assisted by Student Worksheets. With Student Worksheets, students can construct their own knowledge so that students' critical thinking skills can be facilitated and students can play an active role in learning activities, not just doing exercises.Keywords: critical thinking; online learning; student worksheets (LKS).